A scoping review on the clinical effectiveness of Trans-Impedance Matrix (TIM) measurements in detecting extracochlear electrodes and tip fold overs in Cochlear Ltd devices. - Muhammed Ayas; Jameel Muzaffar; Daniele Borsetto; Susan Eitutis; Veronica Phillips; Yu Chuen Tam; Marina Salorio-Corbetto; Manohar L Bance (PLoS ONE, 2024)
Background Extrusion of electrodes outside the cochlea and tip fold overs may lead to suboptimal outcomes in cochlear implant (CI) recipients. Intraoperative measures such as Trans-Impedance Matrix (TIM) measurements may enable clinicians to identify electrode malposition and direct surgeons to correctly place the electrode array during surgery. Objectives To assess the current literature on the effectiveness of TIM measurements in identifying extracochlear electrodes and tip fold overs. Methods A scoping review of studies on TIM-based measurements were carried out using the Databases-Medline/PubMed, AMED, EMBASE, CINAHL and the Cochrane Library following PRISMA guidelines. Eleven full texts articles met the inclusion criteria. Only human studies pertaining to TIM as a tool used in CI were included in the review. Further, patient characteristics, electrode design, and TIM measurement outcomes were reported. Results TIM measurements were available for 550 implanted ears with the subjects age ranged between 9 months to 89 years. Abnormal TIM measurements were reported for 6.55% (36). Tip fold over was detected in 3.64% (20) of the cases, extracochlear electrodes in 1.45% (8), and 1.45% (8) were reported as buckling. Slim-modiolar electrode array designs were more common (54.71%) than pre-curved (23.34%) or lateral wall (21.95%) electrode array. Abnormal cochlear anatomy was reported for five ears (0.89%), with normal cochlear anatomy for all other patients. Conclusion TIM measurement is a promising tool for the intraoperative detection of electrode malposition. TIM measurement has a potential to replace intraoperative imaging in future. Though, TIM measurement is in its early stages of clinical utility, intuitive normative data sets coupled with standardised criteria for detection of abnormal electrode positioning would enhance its sensitivity.